Risk-return analysis of sector the Malaysian residential property sector / Ting Kien Hwa and Mohd Salim Jasiman - Ting, Kien Hwa; Jasiman, Mohd Salim (Faculty of Architecture, Planning & Surveying, 2004)
This paper examines the performance of Malaysian residential property sectors between 1989 - 2001, focusing on risk-return, comparison of residential risk-adjusted performance with equity investments, and identification of risk reduction benefits through portfolio diversification. Performance of residential properties is compared on a risk-adjusted basis with shares. In addition a further analysis is carried out to identify the risk reduction benefits of adding properties to an investment portfolio through diversification. The results show that in terms of residential property type, detached houses provide higher capital appreciation compared to other forms of housing. But the higher returns are associated with higher risks. The best states to invest in residential properties are Kuala Lumpur, Penang and Johor. In terms of regions, investment performance is highest in Johor Bahru followed by Penang Island and Klang Valley. On an inter-asset comparison basis, the best risk-adjusted performance comes from detached and semi-detached houses in Kuala Lumpur which have outperformed shares represented by the Kuala Lumpur Composite Index. For individual investors, the better direct residential property performance over shares clearly identifies the residential property sector as a comparatively attractive investment option. In conclusion, Malaysian residential properties in selected states and by types have performed well and individual investors could enjoy considerable risk reduction by incorporating residential properties in their investment portfolios.